No Long-Term Effect of Physical Activity Intervention on Working Memory or Arithmetic in Preadolescents - Sjöwall, Douglas; Hertz, Mattias; Klingberg, Torkel (Frontiers in Psychology, 2017)
We investigate if increased physical activity leads to enhanced working memory capacity and arithmetic performance, in a 2-year school-based intervention in preadolescent children (age 6-13). The active school (n = 228) increased physical activity (aimed at increasing cardiovascular fitness) from 2 to 5 days a week while the control school (n = 242) remained at 2 days. Twice a year, participants performed tests of arithmetic as well as verbal and spatial working memory. They also rated stress with a questionnaire at the start and at the end of the intervention. There was no beneficial development of working memory or arithmetic for the active school as compared to the control school. Furthermore, subgroup analyses revealed no favorable intervention effect for high/low baseline fitness, cognition or grit. Unexpectedly, a significant increase in self-rated stress was detected for the active school and this effect was driven by girls rather than boys and by the younger rather than older children. These results indicate that longtime high intensity physical activity does not lead to a beneficial development of working memory or arithmetic in preadolescent children.